The organizational climate in Indonesian Islamic banks: A conceptual determination for organizational growth - Ilmi, Muhammad Bahrul (Journal of Accounting and Investment, 2023)
Research aims: This study aims to investigate the growth of Indonesian Islamic banks and explore the determinants of organizational growth from different perspectives through climate factors, namely clarity, standard, commitment, communication, responsibility and teamwork, and support. The study also attempts to develop a model to measure the growth of Islamic banking institutions. Only limited studies have thus far explored this issue, with this study trying to fill the gap. Design/Methodology/Approach: This paper drew upon theories and arguments from the “climate” and “growth” areas and identified organizational climate as one of the main topics affecting Islamic banks. Grounded in a review of the mutual impact of organizational climate and growth constructs, the authors developed research propositions and discussed the implications of the proposed relationships for both. Research findings: Despite Islamic banks having been established and prospered for 28 years, supported by Indonesia having the largest Muslim population of any country in the world, the development of Islamic banks in Indonesia has been inferior to that of conventional banks. This paper argues that organizational climate must be considered an important factor in enhancing Indonesian Islamic banks’ quality. It is because the essence of its climate may help an organization become more effective and generate a better perception, with the climate being used to improve the organization’s quality of management. Theoretical contribution/Originality: By combining the aspects of “climate” and “growth” from earlier studies and categorizing them by organizational studies and a comprehensive literature review, this study proposes a model specific to the banking institution. The study offers a conceptual model for the organizational climate in Islamic banking institutions and argues that organizational climate can be used to determine organizational growth in Indonesian Islamic banks. Practitioner/Policy implication: Based on its proposed conceptual model, this study is expected to contribute knowledge of Indonesian Islamic banks, policies, stakeholders, regulators, and government. The research explores various related studies in organizational growth from a climate perspective. Further, this study’s results will be of significant practical assistance to the managers of Islamic banks and policymakers in developing climate mechanisms for Islamic banking growth. Moreover, this study significantly contributes to economic growth’s sustainability and enhances banks’ growth. Research limitation/Implication: While several factors may be used to predict and determine growth, this study used climate factors to determine the growth of Islamic banking institutions. Thus, it is necessary to explore various factors to develop further studies and add new insight to determine organizational growth.